Efficacy of partial treatment of wheat with spinosad against Rhyzopertha dominica (F.) adults - Subramanyam, Bhadriraju; Boina, Dhana Raj; Sehgal, Blossom; Lazzari, Fernanda (My University, 2015)
The efficacy of partial treatment of wheat with spinosad against adults of the lesser grain borer, Rhyzopertha dominica (F.), was evaluated by mixing spinosad-treated and untreated wheat kernels in varying proportions. Spinosad was applied to wheat kernels either by dipping in 1 mg (a.i.) mlˉ¹ spinosad solution for 1 minute or admixed with dry and liquid spinsoad formulations at 0.1 and the labeled rate of 1 mg (a.i.) kgˉ¹ of wheat. In the kernel dipping method, the percentage of kernels treated was increased from 10 to 100 in 10% increments, while keeping the total number of kernels at either 10 or 100. The mortality of introduced adults in independent samples was observed over time at 1 to 209 h post-infestation. In the admixture method, the percentage of spinosad-treated wheat ranged from 10 to 100 in 10% increments by varying amounts of spinosad-treated and untreated wheat to form a total of 50 g. Mortality of introduced R. dominica adults was determined after 1, 3, 5, and 7 d. In the kernel dipping method, there was an inverse relationship between lethal times for 50 and 95% mortality of R. dominica adults and percentage of kernels treated. In the admixture method, adult mortality increased with an increase in spinosad rate, exposure time, and percentage of kernels treated. The liquid formulation was more effective against R. dominica than the dry formulation. At the labeled rate of 1 mg (a.i.) kgˉ¹, treating 20 to 90% of the kernels with liquid or dry formulation of spinosad was as good as treating 100% of the kernels in controlling R. dominica adults within 3 to 5 d. In practical situations where uneven distribution of spinosad on kernels is expected, complete control of R. dominica adults can be achieved if more than 50% of the kernels receive spinosad treatment.
Keywords: Rhyzopertha dominica; Spinosad; Partial grain treatment; Efficacy